The generic position of the Nubian Bustard Neotis nuba (Cretzschmar, 1826) (Aves: Otididae) - Collar, Nigel J.; Kirwan, Guy M. (Zootaxa, 2023)
The bustard genera Neotis and Ardeotis are generally considered to comprise four species each, but a 2002 molecular phylogeny found N. heuglinii interposed between two pairs of Ardeotis, with N. nuba basal to all seven others. In the absence of a new molecular study one approach to clarifying relationships in the Otididae is to examine the degree of difference in their self-advertisement displays (as performed solitarily, i.e., with no nearby conspecifics). In this regard N. nuba emerges as unique for possessing a strutting parade with its tail raised in a vertical fork, in complete contrast to the neck-inflation displays of other Neotis (which involve no use of the tail) and of all Ardeotis. The tail-fork in N. nuba, unknown in any other bustard, results from the outer rectrices being longer, stiffer and more pointed than the central ones. The species is also unique among bustards in its long broad sandy-rufous crown-stripe; and unlike all other Neotis the sexes are virtually alike in plumage. We consequently propose a new genus Nubotis for N. nuba. Furthermore, we suggest that confirmation of all components of the displays of N. heuglinii, N. denhami and N. ludwigii might precipitate a new genus for N. heuglinii. Fuller review of the distinctions between the Afrotropical A. arabs and A. kori on the one side and the non-Afrotropical A. nigriceps and A. australis on the other might also lead to the reinstatement of Austrotis for the latter two.